ChemInform Abstract: Synthesis of Multisubstituted Dihydroquinoxaline Derivatives by Tandem N‐Alkylation and Addition Reactions of 3‐Oxoquinoxaline‐2‐carboxylates. Issue 37 (September 2015) - Miyamaru, Satoru; Umezu, Kazuto; Ito, Akinori; Shimizu, Makoto
Abstract The one‐pot synthesis of dihydroquinoxalin‐2‐ones is described using an umpolung N‐alkylation followed by oxidation and C‐alkylation reactions.